EKSTRAKSI ANTOSIANIN DARI BIJI ALPUKAT SEBAGAI PEWARNA ALAMI - Achmad, Zubaidi; Sugiarto, Bambang (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
The needs for colorant is increasing, so the colorant produced by natural substances begin to be substituted for synthetic colorant as technology and knowledge develop. The substitution can reduce production cost, but the synthetic colorants have negative effects. The synthetic colorants can be dangerous to our health and environment if they are used for food colorants and textile industry. Therefore, natural substances such as avocado seeds are still needed for coloring which is eco-friendly by applying science and technological development. This research aim to study the effect of extraction time and the ratio of solvent concentration to the concentration of anthocyanin extract and find good conditions in the anthocyanin color test process with the extraction time and the ratio of solvent concentration variable. This research has been carried out through 4 (four) stages: (i) extracting anthocyanin, (ii) separating the anthocyanin extract uses a solvent, (iii) coloring the fabric uses anthocyanin extract which is more concentrated, (iv) testing the anthocyanin colorant by washing it uses detergent. Dissolved anthocyanin concentration analysis is carried out with a UV-Visible Spectrophotometer. This method is applied for discovering the quantity of anthocyanins dissolved in the detergent solution after washing the cloth that has been colored. The research indicate that the largest anthocyanin extract is 0.10002 mL anthocyanin /mL solvent when the extraction time is 150 minutes and the ratio of solvent concentration is 1:13.